Analisis Perlindungan Foto Atau Video Influencer Review Untuk Kepentingan Komersial: Studi dari Undang-Undang Hak Cipta - Bella, Revallinda Salsa; Setianingrum, Reni Budi (University of Merdeka Malang, 2024)
ABSTRAK The development of internet technology has transformed conventional life into digital, eliminating distance and time barriers and encouraging electronic transactions. E-commerce is now an essential part of online business activities, encompassing marketing, sales, and payments. Influencers on platforms such as Instagram and TikTok play a significant role in influencing consumers to shop online. However, it is often the case that their product review photos or videos are taken without permission by other parties for promotion, which constitutes copyright infringement. For example, the copyright infringement case by the Shopee account against TikTok influencer @softdescent3d. Law Number 28 Year 2014 on Copyright regulates the legal protection of photographic works for commercial purposes without permission. This research aims to explore the legal protection of influencer photos or videos and the remedies that aggrieved influencers can take. The method used is normative juridical, with approaches including statute and case approaches. The result of this research is that legal protection of influencer photo or video reviews is very important because copyright gives exclusive rights to the creator, including moral rights and economic rights. Influencers have a great influence on purchasing decisions, but unauthorized use of their work infringes copyright and can manipulate consumers. Legal protection is necessary to safeguard the rights of creators and ensure they get the economic benefits they deserve.